Strategies for Utilizing Village Funds to Improve Community Welfare in Cariu Village, Cariu District, Bogor Regency - Olga Syalwa Deivhilla; Dedeh Mariyani; Sri Hartati (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
Poverty has become a problem in various regions, including in Cariu Village, with a rapid increase in 2022 due to a decline in household income caused by job losses, particularly in the health sector. This area is recorded as a stunting locus, proving that 14% of children experience growth and developmental issues due to chronic malnutrition. Community development and empowerment are greatly needed in situations like this, and Cariu Village has successfully reduced the poverty rate within just one year. Therefore, the researcher wants to understand how to utilize the funds owned by the village, especially village funds, to improve community welfare, as well as the factors that hinder the implementation of the strategy for using village funds to enhance the welfare of the village community, and what efforts are being made to improve the welfare of the village community. The method used is qualitative descriptive, with data collection techniques employing observations, interviews, and documentation, which are then validated using triangulation techniques to be summarized and presented, enabling conclusions to be drawn. The results of this study indicate the success of the strategy created and implemented by the Cariu Village Government in enhancing the welfare of the community as it successfully reduced the poverty rate from 2022 to 2023. By utilizing village funds, Cariu Village is able to facilitate the community in improving the quality of their lives, especially in the fields of development and empowerment, although in its implementation there are still many obstacles ranging from limited budgets, lack of communication and coordination, absence of motivation among officials, to journalists whose visits become a burden for the village government. However, from every obstacle that occurs, there is always a solution carried out, one of which is most often done weekly, namely morning assembly, then briefing of the staff and capacity building of village apparatus as a forum for evaluation, conducting transfers of staff to the dismissal of staff who are no longer effective in their work, as well as setting aside a small portion of the village's original income as a form of handling obstacles coming from the external scope.